PENGEMBANGAN MODUL KURIKULUM MERDEKA PEMBELAJARAN IPAS MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI DALAM MENINGKATKAN PRESTASI BELAJAR - Firsta Bagus Sugiharto; Kardiana Metha Rozhana; Luluk Nurjanah (Universitas Tribhuwana Tunggadewi, 2024)
This research aims to determine the validity of the IPAS (natural and social sciences) module on plant sources of life which can improve learning achievement in the grade IV independent curriculum at SDN 06 Kalipare, Malang Regency. This type of development research uses the Modified ADDIE development model. Data collection instruments include questionnaires for linguists, material experts and media experts. The results of research on the development of the science and science module on plants as the source of life showed an average result of 89.33% with details of 98% for language experts, 90% for material experts and 80% for media experts. From this data it can be concluded that the development of the science and science module is valid and can be used in the science and science learning process regarding plants that are the source of life in the Merdeka curriculum.